Variação inter-sexual na frequência de cromossomos Bs em Corydoras aeneus (Siluriformes: Callichthyidae) - Pacheco, Ana Carolina Sales [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The genus Corydoras, the highest among the Siluriformes, Callichthyidae is owned by the family, consisting of 177 valid species and widely distributed in cis-Andean portion of South America How striking feature has two longitudinal series of dermal plates covering almost the entire body. Cytogenetic studies in Callichthyidae show many chromosomal rearrangements, including events of polyploidy in their evolutionary history, particularly the genus Corydoras, in which the variation is the diploid number of 2n = 40 to 2n = 134 chromosomes. The absence of information on the frequency of chromosomes in the group Bs motivated this work with the species Corydoras aeneus. A population from the Tietê River basin in Ribeirão Claro (subbasin Corumbataí - Rio Claro, SP) was sampled a total of 20 subjects (10 males and 10 females) and 30 metaphases per individual were analyzed cytogenetically. Were carried out by impregnation techniques silver (Ag-NOR). The observed modal diploid number was 2n = 60 (26m +26 sm +8 st), with the variable occurrence of 1 or 2 Bs chromosomes in males and a B chromosome in females, both acrocentric. Regarding the variation in the frequency of chromosome Bs, the occurrence of two B chromosomes is directly linked to males, because there were no female sampled with the occurrence of two chromosomes Bs The low frequency of Bs in females suggests that this event can be sporadic this sex, different from males in which this appears to be set supernumerary chromosome showing a higher frequency of 2 Bs than the actual modal number of 2n = 60. Further studies will be performed to understand the dynamics of the B chromosome in the population

O gênero Corydoras, o maior entre os Siluriformes, é pertencente a família Callichthyidae, constituído de 177 espécies validas e amplamente distribuído na porção cis-andina da América do Sul. Como característica marcante possui duas séries longitudinais de placas dérmicas revestindo quase todo o corpo. Estudos citogenéticos em Callichthyidae mostram muitos rearranjos cromossômicos, incluindo eventos de poliploidia na sua história evolutiva, particularmente no gênero Corydoras, no qual a variação do número diplóide é de 2n=40 a 2n=134 cromossomos. A ausência de informação sobre a freqüência de cromossomos Bs no grupo motivou o presente trabalho com a espécie Corydoras aeneus. Uma população proveniente da bacia do rio Tietê no Ribeirão Claro (sub-bacia do rio Corumbataí - Rio Claro, SP) foi amostrada totalizando 20 indivíduos (10 Machos e 10 Fêmeas) e 30 metáfases por indivíduo foram analisadas citogeneticamente. Foram realizadas as técnicas de impregnação pela prata (Ag-NOR). O número diplóide modal observado foi de 2n=60 (26m+26sm+8st), com a ocorrência variável de 1 ou 2 cromossomos Bs em machos e 1 cromossomo B nas fêmeas, ambos acrocêntricos. Em relação à variação na freqüência de cromossomos Bs, a ocorrência de 2 cromossomos B está diretamente ligada ao sexo masculino, pois não foi encontrada nenhuma fêmea amostrada com a ocorrência de 2 cromossomos Bs. A baixa freqüência de Bs em fêmeas sugere que este evento possa ser esporádico neste sexo, diferente dos machos no quais este cromossomo supranumerário parece estar fixado mostrando uma freqüência maior de 2 Bs do que o próprio número modal de 2n=60. Novos estudos serão realizados para compreender a dinâmica do cromossomo B na população
Keywords: Cromossomos; Bagre (Peixe); Peixe; Citogenética animal